1986
DOI: 10.1007/bf00965162
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of ethanolamine in neuronal and glial cell cultures

Abstract: The uptake of radioactive ethanolamine has been studied in exclusively neuronal and glial cell cultures from dissociated cerebral hemispheres of chick embryos. Both cell types show saturable kinetics; neurons have an apparent Km of 6.7 microM, Vmax 41.4 pmol mg prot.-1 min-1 and glial cells a Km of 119.6 microM, Vmax 3,917 pmol mg prot-1 min-1. The lower affinity of the transport and the 100 fold increase in Vmax observed in glial cells correlated with a more important accumulation of free ethanolamine found i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The temporal cortex shows the most severe reduction in Etn [ 11,281, with the largest degree of neuronal loss and the highest incidence of the neuropathologic markers of A. D. [24]. Thus, the depletion of Etn could be due to the severe loss of neurons, which are known to have a higher affinity for Etn uptake than glial cells [26]. Other mechanisms contributing to the Etn reduction found in A. D., but not yet examined, could include decreased blood levels of Etn, or its decreased absorption from the intestinal lumen.…”
Section: Discussionmentioning
confidence: 99%
“…The temporal cortex shows the most severe reduction in Etn [ 11,281, with the largest degree of neuronal loss and the highest incidence of the neuropathologic markers of A. D. [24]. Thus, the depletion of Etn could be due to the severe loss of neurons, which are known to have a higher affinity for Etn uptake than glial cells [26]. Other mechanisms contributing to the Etn reduction found in A. D., but not yet examined, could include decreased blood levels of Etn, or its decreased absorption from the intestinal lumen.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of myo -inositol selected was based on the findings from Novak et al, who demonstrated that differentiated human central nervous system neurons (NT2-N neurons) have a maximal velocity of inositol uptake ( V max ) of 3.7 nmol/mg-protein/h when treated with various concentrations of inositol ranging from 0 to 500 μM. The concentration of ethanol­amine was chosen on the basis of a report showing that the maximum ethanol­amine uptake for neuronal cells is 41.4 pmol/mg-protein/min . A combination of myo -inositol + ethanol­amine treatment (ME) was investigated since PE-Pls biosynthesis requires the ethanol­amine-derived CDP-ethanol­amine in the pathway, and our laboratory has previously shown that this combination treatment leads to enhanced biosynthesis of ethanol­amine phospho­lipids in rat brain in vivo . The 24 h optimal incubation time was determined in a separate series of experiments in which cells were cultured in growth medium supplemented with ME for 24, 48, and 72 h. The amounts of PE-Pls (nmol/mg protein) obtained with these incubation times were not significantly different ( p < 0.05; data not shown).…”
Section: Methodsmentioning
confidence: 99%
“…A first suggestion came from the neuronal cells' ability to use EA as a precursor of ACh. In chicken neuronal cultures, it was proved that EA is rapidly phosphorylated to phosphoethanolamine and converted to phosphatidylethanolamine that may also be methylated to phosphocholine (18). In vivo, intraventricular injections of 3 H-EA showed that the rat brain has the capacity to synthetize free choline de novo by stepwise methylation of EA, phosphoethanolamine and phosphatidylethanolamine (19).…”
Section: Oea Influences Cholinergic-mediated Food-reward Regulationmentioning
confidence: 99%